Design and Implementation of a Georeferenced Multi-Sensor System for Monitoring Volcanic Gases - Flores Cortez, Omar Otoniel; Pocasangre, Carlos Osmin; Arévalo, Fernando; Rivera Machado, Bryan (LACCEI, 2025)
This paper presents the development and evaluation of a low-cost multisensor system to monitor volcanic gas emissions, focusing on CO2, SO2, and H2S. The performance of the system was validated through field tests conducted at critical sites, including the crater rim of the Santa Ana volcano and the thermal area of Los Infiernillos on the slopes of the San Vicente volcano. Comparison with commercial equipment from the Ministry of Natural Resources (MARN) of El Salvador revealed minor deviations from the measurement, demonstrating the system’s ability to provide reliable data while capturing rapid fluctuations and peak concentrations. This work aims to serve as a low-cost technological tool to achieve effective volcanic risk management and environmental monitoring efforts.